The Usefulness of a Preoperative Nomogram for Predicting the Probability of Conversion from Laparoscopic to Open Distal Pancreatectomy: A Single-Center Experience - Casadei, Riccardo (World J Surg, 2020)
BACKGROUND: Laparoscopic distal pancreatectomy (LDP) represents a challenging procedure with a high conversion rate. A nomogram is a simple statistical predictive tool which is superior to risk groups. The aim of this study was to develop and validate a preoperative nomogram for predicting the probability of conversion from laparoscopic to open distal pancreatectomy. METHODS: This is a retrospective study of 100 consecutive patients who underwent LDP. For each patient demographic, pre-intra- and postoperative data were collected. Univariate and multivariate analyses were carried out to identify the factors significantly influencing the conversion rate. The effect of each factor was weighted using the beta coefficient (β), and a nomogram was built. Finally, a logistic regression between the score and the conversion rate was carried out to calibrate the nomogram. RESULTS: The conversion rate was 19.0%. At multivariate analysis, female (β =  − 1.8 ± 0.9; P = 0.047) and tail location of the tumor (β =  − 2.1 ± 1.1; P = 0.050) were significantly related to a low probability of conversion. Body mass index (BMI) (β = 0.2 ± 0.1; P = 0.011) and subtotal pancreatectomy (β = 2.4 ± 0.9; P = 0.006) were factors independently related to a high probability of conversion. The nomogram constructed had a minimum value of 4 and a maximum value of 18 points. The probability of conversion increased significantly starting from a minimum score of 6 points (P = 0.029; conversion probability 14.4%; 95%CI, 1.5–27.3%) up to 16 (P = 0.048; 27.8%; 95%CI, 0.2–48.7%). CONCLUSION: The nomogram proposed could serve as an effective preoperative tool capable of assessing the probability of conversion, allowing to take reliable decisions regarding indications and adequate stepwise training program of LDP.